Comparison of laparoscopic versus open radical hysterectomy in patients with early‐stage cervical cancer: a multicenter study in China. Issue 8 (August 2020) - Hu, Ting wen yi; Huang, Yue; Li, Na; Nie, Dan; Li, Zhengyu
ABSTRACT : Introduction : Recently, the safety of minimally invasive surgery in the treatment of cervical cancer has been questioned. This study was designed to compare the disease‐free survival and overall survival of abdominal radical hysterectomy and laparoscopic radical hysterectomy in patients with early‐stage cervical cancer. Methods : A total of 1065 patients with early‐stage cervical cancer who had undergone abdominal/laparoscopic radical hysterectomy between January 2013 and December 2016 in seven hospitals were retrospectively analyzed. The 1:1 propensity score matching was performed in all patients. Patients with tumor size ≥2 cm and <2 cm were stratified and analyzed separately. Disease‐free survival and overall survival were compared between matched groups. After conﬁrming the normality by the Shapiro‐Wilks test, the Mann‐Whitney U test and the χ 2 test were used for the comparison of continuous and categorical variables, respectively. The survival curves were generated by the Kaplan‐Meier method and compared by log‐rank test. Results : After matching, a total of 812 patients were included in the disease‐free survival and overall survival analyses. In the entire cohort, the laparoscopic radical hysterectomy group had a significantly shorter disease‐free survival (HR 1.65, 95% CI 1.00 to 2.73; p=0.048) but not overall survival (HR 1.60, 95% CI 0.89 to 2.88; p=0.12) when compared with the abdominal radical hysterectomy group. In patients with tumor size ≥2 cm, the laparoscopic radical hysterectomy group had a significantly shorter disease‐free survival (HR 1.93, 95% CI 1.05 to 3.55; p=0.032) than the abdominal radical hysterectomy group, whereas no significant difference in overall survival (HR 1.90, 95% CI 0.95 to 3.83; p=0.10) was found. Additionally, in patients with tumor size <2 cm, the laparoscopic radical hysterectomy and abdominal radical hysterectomy groups had similar disease‐free survival (HR 0.71, 95% CI 0.24 to 2.16; p=0.59) and overall survival (HR 0.59, 95% CI 0.11 to 3.13; p=0.53). Conclusion : Laparoscopic radical hysterectomy was associated with inferior disease‐free survival compared with abdominal radical hysterectomy in the entire cohort, as well as in patients with tumor size ≥2 cm. For the surgical treatment of patients with early‐stage cervical cancer, priority should be given to open abdominal radical hysterectomy.